Molecular Dynamics Simulation on the Frictional Behavior and Mechanisms of Graphene, Boron Nitride and Their Doping Structures - Li, Zhangchao (International Journal of Materials Science and Technology Studies, 2025)
By establishing a boron nitride-doped graphene system and using molecular dynamics simulation to measure and characterize its frictional behavior, it was found that the doping of boron nitride significantly affects the friction behavior of graphene. this study focuses on the outer layer of pinned atoms on the indenter that have a decisive influence on the friction performance and calculates the resistance of such atoms during the sliding process of the indenter. In addition to the van der Waals cohesive energy, the deformation of the 2D film near the pinned atoms is also studied. The results show that boron nitride doping not only reduces the friction resistance of graphene, but also changes the friction peak value from a basically constant state to a large amplitude and long-period oscillation. Here, changes in the frictional properties and behavior of the doped graphene can be attributed to higher cohesive energy between boron nitride and the indenter, lower adhesion/frictional resistance, and lower strain of the doped graphene around the pinned atoms.